Dynamics of hindered CF3-rotor in 2,5-bis (trifl uoromethyl )-nitroben zene radical -anion in anhydro us DMF. A temperature - activation theory of reversible HFS transformations of EPR spectrum - E. A. Polenov; P. V. Melnikov (Тонкие химические технологии)
The temperature dependence of EPR spectrum of 2,5-bis(trifluoromethyl)nitrobenzene radical anion in anhydrous DMF was investigated. Internal dynamics of hindered rotation of the CF3-group in ortho-position to NO2-group causes HFS modulation. The spectrum changes are reversible and temperature-dependent. An original temperature-activation representation of complex spectral density was proposed instead of the traditional spectral-kinetics representation to explain the observed transformation. The change resulted in a new convenient phenomenological reconstruction model, which allowed simulating the spectra in the whole temperature range. Splitting constants and contributions to the spectral widths of the spectral lines were found. The activation energy of the CF3-group hindered rotation is significant and amounts to 37 kJ/mol.